Overview of Managing Management Information Systems on Supply Chain Management : A Bibliometric Study - Dewi, Rina; Ilham; Suwangsih, Iwang (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2024)
Changes already moved on to manage Management Information System (MIS) in Supply Chain Management (SCM) in business and industry. It coerces an organisation to be competitive in an intense competition. This study aimed to examine the visual map and international research status of the MIS' impact on SCM on Scopus search engines. This study used bibliometric and Scopus with the assistance of Vosviewer to identify and analyse relevant research. There were 381 articles issued between 1994 to 2020. The result showed that the most prolific affiliation was Hong Kong Polytechnic University, and the area that most discussed the impact of MIS on SCM was Computer Science. This study proposed a convergent classification of the MIS effect to SCM into 5 clusters, i.e. Supply Chain Management (SCM), Enterprise Resources Planning (ERP), Decision Support System (DSS), Informatic Management System (IMS), and Knowledge Management (KM).